Bound hydrogenic states in a magnetic field: A finite-difference approach - De Souza, Gustavo Vanin Bernardino [UNESP]; Bruno-Alfonso, Alexys [UNESP] (World Scientific Publishing, 2009)
A finite-difference scheme is used to calculate bound electronic states of an electron in a hydrogen atom subject to a magnetic field. The numerical results are in good agreement with exact results, in the absence of the magnetic field, and with a two-parameters variational calculation, when the magnetic field is applied. © 2009 World Scientific Publishing Company.
Keywords: Finite-difference; Hydrogen; Magnetic field